Going Asexual: A Survey of Mites of the Genus Thyreophagus (Acari: Acaridae) Revealing a Large Number of New Parthenogenetic Species in the Holarctic Region - Klimov, Pavel B.; Kolesnikov, Vasiliy B.; Demard, Emilie P.; Stinson, Clive S. A.; Merckx, Jonas; Duarte, Marcus V. A.; Pedroso, Luiz Gustavo A. [UNESP]; Khaustov, Alexander A.; Myers-Hansen, James Leslie; Wäkers, Felix L.; Vangansbeke, Dominiek (MDPI, 2023)
Mites of the genus Thyreophagus (Acari: Acaridae) are distributed worldwide; they inhabit concealed habitats and include several beneficial and economically important species. However, species identification is difficult because many species are poorly described or delimited and their phoretic stages are unknown or uncorrelated. Furthermore, Thyreophagus is interesting because it includes entirely asexual (parthenogenetic) species. However, among the 34 described species of Thyreophagus, the asexual status is confirmed through laboratory rearing for only two species. Here, we provide detailed descriptions of five new species from North America (four) and Europe (one) based on adults and phoretic heteromorphic deutonymphs. Four of these species were asexual, while one was sexual. For most of these mites, the asexual status was confirmed and phoretic deutonymphs were obtained through rearing in the lab. We show that asexual mites retain seemingly functional copulatory and sperm storage systems, indicating that these lineages have relatively short evolutionary lifespans. One North American species, Thyreophagus ojibwe, was found in association with the native American chestnut Castanea dentata, suggesting a possibility that this mite can be used to control chestnut blight in North America. We also provide a diagnostic key to females, males, and heteromorphic deutonymphs of the Thyreophagus species in the world.
Keywords: astigmatid mites; Europe; factitious food source; morphology; new species; North America; parthenogenetic species; systematics